The Use of Animation Media for the Understanding of the Concept of Letter Recognition in Early Childhood - Marhamah, Ainun; Wahira; Asrifan, Andi; Herlina (International Journal on Education Issues, 2026)
Purpose – Early childhood literacy serves as a vital foundation for academic success, yet traditional teaching methods often struggle to maintain engagement and clarity in letter recognition. This study investigates the influence of animation media on children’s conceptual understanding of letters, specifically focusing on visual shapes, names, and phonemic sounds. Design/Methodology/Approach – The research employed a pre-experimental one-group pretest-posttest design involving children aged 4–6 years. Data were collected through quantitative letter recognition tests and qualitative teacher observations and questionnaires. The study utilized data triangulation—combining performance scores with behavioral observations—to ensure a comprehensive analysis of the media's impact. Findings – The findings indicate a significant improvement in early literacy skills following the intervention. Before the treatment, children demonstrated low baseline scores, particularly in distinguishing mirror-image letters (e.g., b–d, p–q) and consistent phonetic naming. After learning through animation media, children showed a marked increase in visual recognition accuracy and verbal confidence. Qualitative data revealed that the classroom atmosphere became more conducive to learning, with children showing higher levels of enthusiasm and sustained attention compared to conventional methods. Originality/Value – The results demonstrate that animation media effectively bridges the gap between abstract symbols and concrete cognitive understanding by providing multisensory stimulation. Unlike generic entertainment content, the structured instructional design of the media used in this study successfully balanced digital engagement with pedagogical goals. This study concludes that animation media is a feasible, relevant, and effective tool for early childhood education, serving as a practical reference for educators to modernize literacy instruction.